A new species of Palaeugoa Durante, 2012 from Sierra Leone (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V. (Zootaxa, 2017)
The Asura / Miltochrista generic complex (family Erebidae, subfamily Arctiinae, tribe Lithosiini) is one of the largest and taxonomically most difficult Lithosiini groups widely distributed in Afrotropical, Palaearctic, Oriental, and Indo-Australian regions. In Africa, the generic complex is represented by the genera Tumicla Wallengren, 1863 (= Asuroides Durante, 2008, syn. rev.), Afrasura Durante, 2009, Parafrasura Durante, 2012 and Palaeugoa Durante, 2012. The genus Palaeugoa was erected as monobasic for Xanthetis spurrelli Hampson, 1914 described from Ghana (Durante 2012). During the studies of West African Lithosiini materials deposited in the collection of the African Natural History Research Trust, I found a second, yet undescribed species of Palaeugoa collected in Sierra Leone. The description of the new species is given below.